High-safety composite diaphragm, preparation method thereof and lithium ion battery
Patent Information
- Application Number
- CN202610945810.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-09-08
- Estimated Expiration
- 2046-06-29
AI Technical Summary
[0007]本发明旨在解决现有技术中隔膜安全性不高的问题,提供一种热滥用条件下兼具极速闭孔和高温尺寸稳定性的高安全性复合隔膜及其制备方法和锂离子电池
[0018]Compared with the prior art, this application has the following beneficial effects: In the above-mentioned high-safety composite separator and its preparation method and lithium-ion battery, two dimensionless relationships are defined simultaneously: the thermosensitive pore-closure relationship and the thermal conductivity anisotropy relationship. This achieves synergistic optimization of thermosensitive pore-closure efficiency and thermal conductivity anisotropy, enabling the composite separator to have both extremely fast pore-closure (ionic conductivity drops rapidly to below 10%, usually ≤60s) and high-temperature dimensional stability (the thermal shrinkage rate of the composite separator is less than 5% after being kept at 200°C for 1 hour, and the heat-resistant layer does not crack) under thermal abuse conditions. This suppresses thermal diffusion, with heat preferentially conducted vertically to the thermosensitive layer, and horizontal thermal spread is suppressed. Simultaneously defining two dimensionless relationships ensures a coordinated match between the particle size of the thermistor material, the coating thickness, and the porosity of the base film. Under conditions of thermal abuse, this achieves a rapid decrease in ionic conductivity of over 90%, blocking ion transport and preventing thermal runaway. Combined with vertical magnetic field orientation, the thermal conductivity of vertical and horizontal heat conduction is controlled between 1.2 and 10, ensuring rapid heat transfer from the cell interior to the thermistor layer while suppressing unfavorable heat diffusion within the separator plane, avoiding shrinkage failure of the heat-resistant layer due to localized heat concentration. By defining these cross-coupling relationships, thermal conductivity, pore-closing time, particle size matching, coating thickness, and base film structure are considered holistically, achieving a dynamic balance between heat input and pore-closing requirements, significantly improving the overall safety of the separator. This separator does not rely on specific base film or coating materials and is suitable for porous base films such as polyethylene and polypropylene, as well as various thermistor materials (polyurethane, oxidized polyethylene wax, etc.) and thermally conductive materials (boron nitride, etc.). Furthermore, it can be industrially produced through a magnetic field-oriented coating process.
Smart Images

Figure CN122494994B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium battery technology, and more specifically, to a high-safety composite separator, its preparation method, and a lithium-ion battery. Background Technology
[0002] Lithium-ion batteries are widely used in consumer electronics, electric vehicles, and energy storage due to their high energy density and long cycle life. The separator, as a key component of lithium batteries, functions to isolate the positive and negative electrodes, prevent short circuits, and provide a pathway for lithium-ion transport. The safety performance of the separator directly determines the battery's failure mode under abuse conditions.
[0003] In existing technologies, to improve the safety of the diaphragm, a functional layer is typically coated onto the surface of the base membrane. For example, coating with a ceramic layer can improve the diaphragm's resistance to heat shrinkage and prevent short circuits caused by diaphragm shrinkage at high temperatures; coating with a polymer layer containing heat-sensitive materials (such as polyethylene or polypropylene particles) can melt and close the pores at high temperatures, blocking ion transport and thus inhibiting the further development of thermal runaway.
[0004] However, the existing technology still has the following technical problems:
[0005] First, it is difficult to balance the closed-cell response speed with the thermal shrinkage resistance. Thermistor materials require a certain amount of time to melt and close the cells. If the closing speed is too slow, a large amount of heat will accumulate before the closing is completed, which may lead to the failure of the thermal layer or the overall shrinkage of the separator. Conversely, if the thickness of the thermal layer is increased or its composition is changed in an excessive pursuit of rapid cell closing, it may affect the ionic conductivity and battery rate performance at room temperature.
[0006] Second, thermally conductive materials are usually added uniformly to the separator coating, only to uniformly disperse local heat inside the battery, without taking into account the influence of the thermal conductivity of the thermally conductive material in different directions on the separator performance. Summary of the Invention
[0007] This invention aims to address the problem of low safety of existing separators, and provides a high-safety composite separator that combines rapid pore closure and high-temperature dimensional stability under thermal abuse conditions, as well as its preparation method and lithium-ion battery.
[0008] To achieve the above objectives, the first aspect of this application provides a high-safety composite membrane, comprising: Porous base membrane; A thermosensitive functional layer is disposed on at least one side of the porous base film, the thermosensitive functional layer comprising a thermosensitive material; A heat-resistant functional layer disposed on the porous base film or on the thermosensitive functional layer; The thermally conductive material is dispersed in the heat-sensitive functional layer and / or the temperature-resistant functional layer; the thermally conductive material is oriented in the vertical direction to form an anisotropic thermally conductive network; The composite diaphragm simultaneously meets the following conditions: 3.2≤( D h × C v ) / ( T h × e )≤8.5; and 1.2≤ K v / K h ≤10; in, D h The average particle size of the thermosensitive material is expressed in μm. C v The thickness of the thermally sensitive functional layer is expressed in μm. T h The time required for the ionic conductivity of the composite diaphragm to decrease to 10% of its initial value when the temperature reaches the melting point of the thermosensitive material during a hot box test, in minutes, wherein the heating rate of the hot box test is 1℃ / min to 10℃ / min; e The porosity of the porous membrane is given. K v The thermal conductivity of the thermally conductive material in the vertical direction is expressed in W / (m·K). K h The thermal conductivity of the thermally conductive material in the horizontal direction is expressed in W / (m·K).
[0009] In one embodiment, the thermosensitive functional layer is disposed on both sides of the porous base membrane, and the temperature-resistant functional layer is disposed on the thermosensitive functional layer.
[0010] In one embodiment, when the thermally conductive material is dispersed in the thermosensitive functional layer, the composite membrane also satisfies the following condition: 30≤( K v × T h × D h ) / ( C v × e × d ≤80; in, d The average pore size of the porous membrane is expressed in μm. When the thermally conductive material is dispersed in the heat-resistant functional layer, the composite diaphragm also satisfies the following conditions: 8≤( K v × T h × D h ) / ( C v × e × C c × d ≤50; in, C c The thickness of the heat-resistant functional layer is expressed in μm. d The average pore size of the porous base membrane is expressed in μm.
[0011] In one embodiment, the thickness of the porous base film L The porosity of the porous base membrane is 5μm~12μm. e The average pore size of the porous base membrane is 30%~55%. d The micrometer diameter is 0.01 μm to 0.1 μm, and the air permeability of the porous base membrane is 60 s / 100 mL to 300 s / 100 mL.
[0012] In one embodiment, the thermosensitive material is at least one selected from oxidized polyethylene wax, ethylene-acrylic acid copolymer, Fischer-Tropsch wax, polyurethane, ethylene-vinyl acetate, and polyethylene wax, with a melting point of 90°C to 110°C, and the average particle size of the thermosensitive material is... D h The range is 0.2μm to 2μm, and D h With respect to the average pore size of the porous base membrane d Satisfy: 2≤ D h / d ≤200.
[0013] In one embodiment, the thermally conductive material is boron nitride, graphene, MXene, graphene oxide, or carbon nanotubes.
[0014] In one embodiment, the thickness of the heat-resistant functional layer C c The thickness is 1.5μm to 3.5μm, and the heat-resistant functional layer contains at least one of nano-alumina, aramid, polyimide, and nano-cellulose. The composite membrane has a heat shrinkage rate of less than 5% after being kept at 200°C for 1 hour. The thickness of the thermal functional layer C v The range is 1.5μm to 4μm, and C v With respect to the thickness of the porous base film L The ratio satisfies: 0.15 ≤ C v / L ≤0.45.
[0015] In one embodiment, the amount of thermally conductive material added to the thermistor functional layer accounts for 5% to 10% of the total mass of the thermistor material, and the amount of thermally conductive material added to the heat-resistant functional layer accounts for 8% to 15% of the total mass of the heat-resistant material.
[0016] A second aspect of this application provides a lithium-ion battery, including a positive electrode, a negative electrode, an electrolyte, and a composite separator as described above.
[0017] A third aspect of this application discloses a method for preparing the composite membrane as described above, comprising the following steps: Thermosensitive materials, dispersants, binders and solvents are mixed to obtain a thermosensitive coating slurry; The heat-resistant material, dispersant, binder and solvent are mixed to obtain the heat-resistant coating slurry; Add the thermally conductive material to the heat-sensitive coating slurry and / or the heat-resistant coating slurry and mix evenly; The heat-resistant coating slurry and the thermosensitive coating slurry are applied to the corresponding sides of the porous base film to form a heat-resistant functional layer and a thermosensitive functional layer; the thermosensitive functional layer is disposed on at least one side of the porous base film, and the heat-resistant functional layer is disposed on the porous base film or on the thermosensitive functional layer. When applying a heat-sensitive coating slurry containing thermally conductive material and / or the heat-resistant coating slurry, an electric field or magnetic field is applied to orient the thermally conductive material in a vertical direction, and the composite membrane is obtained after drying.
[0018] Compared with the prior art, this application has the following beneficial effects: In the above-mentioned high-safety composite separator and its preparation method and lithium-ion battery, two dimensionless relationships are defined simultaneously: the thermosensitive pore-closure relationship and the thermal conductivity anisotropy relationship. This achieves synergistic optimization of thermosensitive pore-closure efficiency and thermal conductivity anisotropy, enabling the composite separator to have both extremely fast pore-closure (ionic conductivity drops rapidly to below 10%, usually ≤60s) and high-temperature dimensional stability (the thermal shrinkage rate of the composite separator is less than 5% after being kept at 200°C for 1 hour, and the heat-resistant layer does not crack) under thermal abuse conditions. This suppresses thermal diffusion, with heat preferentially conducted vertically to the thermosensitive layer, and horizontal thermal spread is suppressed. Simultaneously defining two dimensionless relationships ensures a coordinated match between the particle size of the thermistor material, the coating thickness, and the porosity of the base film. Under conditions of thermal abuse, this achieves a rapid decrease in ionic conductivity of over 90%, blocking ion transport and preventing thermal runaway. Combined with vertical magnetic field orientation, the thermal conductivity of vertical and horizontal heat conduction is controlled between 1.2 and 10, ensuring rapid heat transfer from the cell interior to the thermistor layer while suppressing unfavorable heat diffusion within the separator plane, avoiding shrinkage failure of the heat-resistant layer due to localized heat concentration. By defining these cross-coupling relationships, thermal conductivity, pore-closing time, particle size matching, coating thickness, and base film structure are considered holistically, achieving a dynamic balance between heat input and pore-closing requirements, significantly improving the overall safety of the separator. This separator does not rely on specific base film or coating materials and is suitable for porous base films such as polyethylene and polypropylene, as well as various thermistor materials (polyurethane, oxidized polyethylene wax, etc.) and thermally conductive materials (boron nitride, etc.). Furthermore, it can be industrially produced through a magnetic field-oriented coating process. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 A schematic diagram of a method flow for a composite diaphragm according to one embodiment is shown. Detailed Implementation
[0021] To facilitate understanding of this application, the following description will be more comprehensive and detailed in conjunction with the accompanying drawings and preferred embodiments, but the scope of protection of this application is not limited to the following specific embodiments.
[0022] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of this application.
[0023] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0024] A high-safety composite separator according to an embodiment of the present invention includes: a porous base membrane; a thermosensitive functional layer disposed on at least one side of the porous base membrane, the thermosensitive functional layer comprising a thermosensitive material; a temperature-resistant functional layer disposed on the porous base membrane or on the thermosensitive functional layer; a thermally conductive material dispersed in the thermosensitive functional layer and / or the temperature-resistant functional layer; the thermally conductive material is oriented in a vertical direction to form an anisotropic thermally conductive network; the composite separator simultaneously satisfies the following conditions: 3.2≤( D h × C v ) / ( T h × e )≤8.5; and 1.2≤ K v / K h ≤10; in, D h The average particle size of the thermosensitive material is expressed in μm. C v The thickness of the thermally sensitive functional layer is expressed in μm. T h The time required for the ionic conductivity of the composite diaphragm to decrease to 10% of its initial value when the temperature reaches the melting point of the thermosensitive material during a hot box test, in minutes, wherein the heating rate of the hot box test is 1℃ / min to 10℃ / min; e The porosity of the porous membrane is calculated as a decimal value in this application. K v The thermal conductivity of the thermally conductive material in the vertical direction is expressed in W / (m·K). K h The thermal conductivity of the thermally conductive material in the horizontal direction is expressed in W / (m·K).
[0025] Among them, in the thermosensitive closed-cell relationship, D h × C vCharacterizing the "volume pore-closing ability" of the thermosensitive material in the thermosensitive functional layer: the larger the particle size and the thicker the coating, the more pores can be blocked after melting. T h × e The product of the time required for pore closure and the porosity of the base film is used to characterize this. A shorter pore closure time and a lower base film porosity make it easier to achieve rapid ion transport blocking. Experimental design and results demonstrate that 3.2 ≤ ( D h × C v ) / ( T h × e Within this value range, ≤8.5 ensures that the heat-sensitive material can melt rapidly and effectively seal the pores when thermal abuse occurs, while avoiding the increase in room temperature resistance caused by excessive coating thickness or excessive particle size, which may result in incomplete pore closure, easy cracking of the coating, or increased thermal shrinkage.
[0026] Thermally conductive materials are oriented to form an anisotropic network through electric or magnetic fields: thermal conductivity in the vertical direction K v The rapid conduction of heat from inside the cell to the thermistor layer affects the triggering of the closed via; Horizontal thermal conductivity K h The value should be appropriately small to prevent localized heat concentration that could lead to shrinkage and failure of the heat-resistant layer, while also ensuring uniform heat diffusion within the membrane plane. 1.2≤ K v / K h A range limit of ≤10 ensures a balance between fast vertical transmission and slow horizontal transmission. K v / K h When the temperature is below 1.2, vertical thermal conductivity is insufficient, and pore closing is delayed; when it is above 10, horizontal thermal conductivity is insufficient, and the heat inside the cell cannot be homogenized in the separator plane, which can easily lead to discontinuous pore closing.
[0027] Preferably, in one embodiment, the thermosensitive functional layer is disposed on both sides of the porous base membrane, and the heat-resistant functional layer is disposed on the thermosensitive functional layer. When the thermosensitive functional layer is disposed on both sides of the porous base membrane, under thermal abuse conditions (such as internal short circuit, overcharging leading to high temperature), the thermosensitive materials on both sides are heated and melted almost simultaneously, blocking the membrane pores near the positive and negative electrode sides, respectively. The overall pore-closing capacity of the dual-sided thermosensitive layer is enhanced, which can appropriately reduce the pore size of a single side. C v or D hThis reduces the impact on room-temperature ionic conductivity, achieving a better balance between safety and electrical performance. The heat-resistant functional layer is located on the outermost side, directly contacting the high-temperature environment inside the battery cell, providing physical support and a thermal barrier to prevent the thermistor layer from being crushed and damaged by the base film shrinkage or electrode expansion before melting. More preferably, the heat-resistant functional layer contains thermally conductive material and forms a vertical thermally conductive network through orientation induced by an electric or magnetic field. Placing the heat-resistant functional layer on the outermost side allows for more efficient vertical conduction of heat from inside the battery cell to the inner thermistor layer, accelerating the closed-cell triggering.
[0028] Preferably, in one embodiment, when the thermally conductive material is dispersed in the thermosensitive functional layer, the composite diaphragm also satisfies the following condition: 30≤( K v × T h × D h ) / ( C v × e × d ≤80; in, d The average pore size of the porous base membrane is expressed in μm.
[0029] The above relationships take into account that the faster the vertical heat conduction, the shorter the pore closing time, and the larger the particle size, the appropriate thickness, porosity, and pore size of the thermosensitive layer are needed to balance them, so as to prevent the ionic conductivity from being affected at room temperature, and excessive pore closing or heat loss at high temperature.
[0030] Preferably, in one embodiment, when the thermally conductive material is dispersed in the heat-resistant functional layer, the composite diaphragm also satisfies the following condition: 8≤( K v × T h × D h ) / ( C v × e × C c × d ≤50; in, C c The thickness of the heat-resistant functional layer is expressed in μm. d The average pore size of the porous base membrane is expressed in μm. This relationship ensures that heat can effectively penetrate the heat-resistant layer to reach the heat-sensitive layer, while preventing the heat-resistant layer from shrinking due to overheating.
[0031] Preferably, in one embodiment, the thickness of the porous base film... LThe porosity of the porous base membrane is 5μm~12μm. e The percentage is 30% to 55%, which translates to 0.3 to 0.55 decimals, and the average pore size of the porous base membrane is... d The micrometer diameter is 0.01 μm to 0.1 μm, and the air permeability of the porous base membrane is 60 s / 100 mL to 300 s / 100 mL.
[0032] Preferably, in one embodiment, the thermosensitive material is at least one selected from oxidized polyethylene wax, ethylene-acrylic acid copolymer, Fischer-Tropsch wax, polyurethane, ethylene-vinyl acetate, and polyethylene wax, with a melting point of 90°C to 110°C, and the average particle size of the thermosensitive material is... D h The range is 0.2μm to 2μm, and D h With respect to the average pore size of the porous base membrane d Satisfy: 2≤ D h / d ≤200.
[0033] Preferably, in one embodiment, the thermally conductive material is boron nitride, graphene, MXene, graphene oxide, or carbon nanotubes. Utilizing the anisotropic magnetic susceptibility of the thermally conductive material (such as boron nitride, graphene, or MXene), it is aligned along the direction of the magnetic field lines under a strong magnetic field. The orientation can be precisely controlled by changing the direction of the magnetic field. For fillers with polarity or that can be polarized (such as carbon nanotubes or graphene oxide), applying an electric field can orient them along the direction of the electric field.
[0034] Preferably, in one embodiment, the thickness of the heat-resistant functional layer C c The thickness is 1.5μm to 3.5μm, and the heat-resistant functional layer contains at least one of nano-alumina, aramid, polyimide and nano-cellulose. The composite membrane has a heat shrinkage rate of less than 5% after being kept at 200°C for 1 hour.
[0035] Preferably, in one embodiment, the thickness of the thermally sensitive functional layer C v The range is 1.5μm to 4μm, and C v With respect to the thickness of the porous base film L The ratio satisfies: 0.15 ≤ C v / L ≤0.45.
[0036] Preferably, in one embodiment, the amount of thermally conductive material added to the thermistor functional layer accounts for 5% to 10% of the total mass of the thermistor material. When the amount of thermally conductive material added is less than 5%, the heating uniformity of the thermistor functional layer decreases, and the effect of improving the pore-closure efficiency of the thermistor layer is not good; in addition, the thermal conduction pathways in the vertical direction are too sparse, which can easily lead to the expansion of the local overheating area and increase safety hazards; when the amount of thermally conductive material added is more than 10%, it can easily lead to incomplete pore closure of the thermistor layer; in addition, due to the high rigidity of the thermally conductive material, too much thermally conductive material will form sharp "burr" ends during the vertical orientation process. When pressure is applied during battery assembly or the cell expands, these excess thermally conductive materials are very likely to puncture the porous base film, resulting in micro-short circuits. Controlling it to within 10% can ensure that the thermistor functional layer still maintains sufficient flexibility and integrity before melting, avoiding the risk of "point discharge"; and achieve efficient and complete pore closure during high-temperature melting.
[0037] The thermally conductive material added to the heat-resistant functional layer accounts for 8% to 15% of the total mass of the heat-resistant material. If the amount of thermally conductive material added is less than 8%, the thermally conductive material will be covered and isolated by the heat-resistant material during the slurry coating process, which is not conducive to the formation of a thermally conductive network in the vertical direction. The heat-resistant functional layer is located on the outermost layer of the separator and needs to withstand electrolyte immersion and repeated charge-discharge stress. When the amount of thermally conductive material added is higher than 15%, the continuous phase of the polymer binder is severely interrupted, resulting in a sharp decrease in the peel strength between the heat-resistant functional layer and the porous base film (or the thermosensitive functional layer). During long-term battery cycling, excessively high thermally conductive material content will cause the heat-resistant layer to detach and contaminate the electrolyte. Controlling the upper limit to 15% ensures both the structural stability of the separator without shrinkage at 200℃ and the long-term adhesion of the coating in the electrolyte.
[0038] In a second aspect, the present invention also provides a lithium-ion battery comprising a positive electrode, a negative electrode, an electrolyte, and a composite separator as described above.
[0039] Please see Figure 1 A third aspect of the present invention also provides a method for preparing the composite membrane as described above, comprising the following steps: S10. Mix the heat-sensitive material, dispersant, binder and solvent to obtain a heat-sensitive coating slurry; S20. Mix the heat-resistant material, dispersant, binder and solvent to obtain a heat-resistant coating slurry; S30. Add the thermally conductive material to the heat-sensitive coating slurry and / or the heat-resistant coating slurry and mix evenly. S40. The heat-resistant coating slurry and the thermosensitive coating slurry are coated on the corresponding sides of the porous base film using a micro-gravure roller coating process to form a heat-resistant functional layer and a thermosensitive functional layer; the thermosensitive functional layer is disposed on at least one side of the porous base film, and the heat-resistant functional layer is disposed on the porous base film or on the thermosensitive functional layer. S50. When coating the heat-sensitive coating slurry containing thermally conductive material and / or the heat-resistant coating slurry, an electric field or magnetic field is applied to orient the thermally conductive material in a vertical direction, and the composite diaphragm is obtained after drying.
[0040] Specifically, the anisotropy of magnetic susceptibility of thermally conductive materials (such as boron nitride, graphene, and MXene) is utilized to align them along the direction of magnetic field lines under a strong magnetic field. The orientation can be precisely controlled by changing the direction of the magnetic field. For fillers that are polar or can be polarized (such as carbon nanotubes and graphene oxide), applying an electric field can orient them along the direction of the electric field.
[0041] The present invention will be described in detail below with reference to the embodiments, but the present invention is not limited to these embodiments.
[0042] I. Testing Methods The separators and lithium-ion batteries prepared in the following embodiments and the separators and lithium-ion batteries in the comparative examples were tested, and the corresponding test data and results were obtained. The specific tests are as follows: Closure time T h The composite separator was assembled into a CR2032 coin cell, and electrochemical impedance spectroscopy (EIS) was performed using an electrochemical workstation with a frequency range of 1MHz to 0.1Hz. The cell was placed in a hot chamber and heated at 5℃ / min, and the time required for the ionic conductivity to decrease to 10% of its initial value was recorded (the time was zero when the temperature reached the melting point of the thermistor material).
[0043] thermal conductivity K v / K h The thermal conductivity in the vertical and horizontal directions was tested using a Hot-disk TPS 2500S, and the anisotropic test module was used.
[0044] Heat shrinkage rate: Cut the diaphragm into 10cm×10cm samples, place them in a 200℃ oven and keep them warm for 1 hour, and calculate the area change rate, which is the heat shrinkage rate.
[0045] Needle penetration strength: Referring to the standard GB / T36363-2018 "Polyolefin separator for lithium-ion batteries", a needle with a tip curvature radius of 0.5 mm and a diameter of 1.0 mm was used to penetrate vertically at a speed of 2 mm / s, and the maximum force value was recorded.
[0046] Air permeability: The air permeability of the membrane was tested using a Gurley 4110N air permeability meter, in accordance with the standard GB / T36363-2018 "Polyolefin Separators for Lithium-ion Batteries".
[0047] Porosity: The ratio of the amount of absorbance to the membrane volume was calculated using the liquid absorption method (n-butanol).
[0048] Average pore size: measured using a capillary flow pore size analyzer.
[0049] In the following embodiments, the porous base membrane is a polyethylene (PE) membrane or a polypropylene (PP) membrane, the heat-sensitive material is polyurethane or oxidized polyethylene wax, the thermally conductive material is hexagonal boron nitride nanosheets (h-BNNS, average thickness 5nm, lateral dimension 2µm), and the heat-resistant material is nano-alumina (Al2O3, D... 50 =0.5-0.6μm).
[0050] Example 1 The preparation process of the composite membrane is as follows: 1. Mix 342.86g of oxidized polyethylene wax emulsion (solid content 35%), 0.7g of sodium diisooctyl succinate sulfonate (solid content 75%), 38g of polyacrylamide (solid content 20%), 41.58g of polyacrylate (solid content 28.5%) and 376.86g of water to obtain a heat-sensitive coating slurry. 2. Mix 279g of nano-alumina, 33.48g of hexagonal boron nitride nanosheets (12% of the mass of nano-alumina), 1.07g of sodium diisooctyl succinate sulfonate (75% solid content), 100g of sodium carboxymethyl cellulose (2% solid content), 27g of acrylic polymer (40% solid content), 48g of polyacrylamide (20% solid content), 51.58g of polyacrylate (28.5% solid content), and 259.87g of water to obtain a heat-resistant coating slurry containing thermally conductive materials; 3. The thermosensitive coating slurry is coated onto both sides of a 7µm PE base film using a micro-gravure roller coating process. After drying at 40°C, a 2µm thick thermosensitive functional layer is formed. A heat-resistant coating slurry is then coated onto both thermosensitive functional layers and dried at 45°C, forming a 2µm thick heat-resistant functional layer. During the coating of the heat-resistant coating slurry containing thermally conductive material, a vertical alternating electric field (frequency 500Hz, duty cycle 50%, peak voltage 800V) is applied to orient the thermally conductive material vertically. The composite diaphragm is obtained after winding.
[0051] The relevant parameters of the obtained composite membrane are as follows: Porous base membrane: PE membrane, thickness L =7μm, porosity e =37%, average pore size d =0.03μm, needle penetration intensity P p =380gf, air permeability 80s / 100mL.
[0052] Temperature-resistant functional layer: Nano-alumina ceramic layer, thickness C c =2μm.
[0053] Thermosensitive functional layer: Oxidized polyethylene wax (melting point 95℃), average particle size D h =0.5μm, thickness of the thermal layer C v =2μm.
[0054] Thermally conductive material: dispersed in the heat-resistant functional layer, with a content of 12wt% of the mass of nano-alumina, oriented by magnetic field induction (a vertical alternating electric field is applied during coating, with a frequency of 500Hz, a duty cycle of 50%, and a peak voltage of 800V). K v =3.5W / (m·K), K h =2W / (m·K), K v / K h =1.75.
[0055] Test results show the pore-closing time of the composite diaphragm T h =0.5 min.
[0056] ( D h × C v ) / ( T h × e )=5.41 The membrane was tested and found to have a thermal shrinkage rate of 1.2% at 200℃ and an ionic conductivity of 0.63 mS / cm at room temperature.
[0057] Example 2 The preparation process of the composite membrane is the same as that in Example 1, except that: the porous base membrane is a PE membrane with a thickness of... L =9μm, porosity e =45%, average pore size d =0.04μm, needle penetration intensity P p =350gf, air permeability 110s / 100mL.
[0058] Temperature-resistant functional layer: Nano-alumina ceramic layer, thickness C c =2μm.
[0059] Thermosensitive functional layer: Oxidized polyethylene wax (melting point 95℃), average particle size Dh =1μm, thickness of the thermal layer C v =2μm.
[0060] Thermally conductive material: dispersed in the thermistor functional layer, content 8wt%, oriented by magnetic field induction. K v =4W / (m·K), K h =1.8W / (m·K), K v / K h =2.22. The test results show that the pore closure time is... T h =0.7 min.
[0061] ( D h × C v ) / ( T h × e )=6.35 The membrane's heat shrinkage rate at 200℃ was found to be 1.8% after testing.
[0062] Example 3 The preparation process of the composite membrane is the same as that in Example 1, except that: the porous base membrane is a PP membrane with a thickness L = 12 μm, porosity ε = 50%, average pore size d = 0.048 μm, and needle penetration strength... P p =310gf, air permeability 260s / 100mL.
[0063] Temperature-resistant functional layer: Nano-alumina ceramic layer, thickness C c =2μm.
[0064] Thermosensitive functional layer: Polyurethane (melting point 102℃), average particle size D h =1μm, thickness of the thermal layer C v =3μm.
[0065] Thermally conductive material: dispersed in the thermistor functional layer, content 10wt%, oriented by magnetic field induction. K v =4.5W / (m·K), K h =1.6W / (m·K), K v / K h =2.81. The test results show the closure time...T h =0.83 min.
[0066] ( D h × C v ) / ( T h × e )=7.23 The membrane's heat shrinkage rate at 200℃ was found to be 2% after testing.
[0067] Example 4 The preparation process of the composite membrane is the same as that in Example 1, except that: the porous base membrane is a PE membrane with a thickness L = 5 μm, porosity ε = 40%, average pore size d = 0.038 μm, and needle penetration strength... P p =400gf, air permeability 140s / 100mL.
[0068] Temperature-resistant functional layer: Nano-alumina ceramic layer, thickness C c =2.5μm.
[0069] Thermosensitive functional layer: Fischer-Tropsch wax (melting point 100℃), average particle size D h =0.6μm, thickness of the thermal layer C v =2.0μm.
[0070] Thermally conductive material: dispersed in the heat-resistant functional layer, content 15wt%, oriented by magnetic field induction. K v =4.2W / (m·K), K h =1.4W / (m·K), K v / K h =3. Test results show that the closure time is... T h =0.63 min.
[0071] ( D h × C v ) / ( T h × e )=4.76 The membrane's heat shrinkage rate at 200℃ was measured to be 1.6%.
[0072] Comparative Example 1 The difference from Example 1 is that the base film porosity is 40% and the thickness of the thermosensitive layer is [not specified]. C v =4.5μm, thermosensitive particle size D h =2μm. K v =3.5 W / (m·K), K h =2.0 W / (m·K), K v / K h =1.75. The test results show the closure time. T h =7.88 min.
[0073] ( D h × C v ) / ( T h × e =2.86 < 3.2 The membrane's heat shrinkage rate at 200℃ was measured to be 3.6%.
[0074] Comparative Example 2 The difference from Example 1 is the thickness of the thermal layer. C v =5.5μm, thermosensitive particle size D h =5μm. K v =3.0 W / (m·K), K h =2.2 W / (m·K), K v / K h =1.36. The test results show the closure time... T h =8.3min.
[0075] ( D h × C v ) / ( T h × e =8.95 > 8.5 Tests showed that the diaphragm had a thermal shrinkage rate of 9.5% at 200℃ and an ionic conductivity of 0.01 mS / cm at room temperature.
[0076] Comparative Example 3 The difference from Example 1 is that the electric field parameters (frequency 1200Hz, duty cycle 80%, voltage 1500V) are adjusted. K v =6W / (m·K), K h =0.5W / (m·K), K v / K h =12>10. The test results show the closure time. T h =9.63 min.
[0077] ( D h × C v ) / ( T h × e )=0.28 The membrane's thermal shrinkage rate at 200℃ was tested to be 7.5%.
[0078] Comparative Example 4 The difference from Example 1 is that no electric field was applied to induce orientation. K v =1.0W / (m·K), K h =1.3W / (m·K), K v / K h =0.77 < 1.2. The test results show the closure time. T h =12.97 min.
[0079] ( D h × C v ) / ( T h × e )=0.21 The membrane's thermal shrinkage rate at 200℃ was tested to be 12.5%.
[0080] Comparative Example 5 The difference from Example 2 is that there is no heat-resistant layer.
[0081] Test results show the closure time T h =0.67 min.
[0082] Tests showed that the diaphragm completely melted and shrank at 200°C.
[0083] Table 1 Comparative Analysis of Diaphragm Test Data
[0084] As can be seen from the table above, the composite membrane structure configured using the scheme of this application, when 3.2 ≤ ( D h × C v) / ( T h × e )≤8.5 and 1.2≤ K v / K h Only when both ≤10 and other conditions are met can the composite diaphragm achieve rapid pore closure. T h The parameters exhibit excellent dimensional stability at high temperatures (≤60s) and thermal shrinkage rate (≤5% at 200℃). Exceeding either range leads to a significant decrease in safety, demonstrating the criticality and synergy of the parameter ranges in this invention.
[0085] The composite separator provided by this invention can be widely used in lithium-ion batteries, especially power batteries and energy storage batteries with high energy density and high safety requirements. While ensuring electrochemical performance at room temperature, this composite separator significantly improves the safety performance of batteries under thermal abuse conditions, and has promising prospects for industrial application.
[0086] The above are merely preferred embodiments of this application. It should be noted that this application is not limited to the above embodiments. For those skilled in the art, several improvements and modifications can be made without departing from the principles of this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should also be considered within the scope of protection of this application.
Claims
1. A high-safety composite diaphragm, characterized in that, include: Porous base membrane; A thermosensitive functional layer is disposed on at least one side of the porous base film, the thermosensitive functional layer comprising a thermosensitive material; A heat-resistant functional layer is disposed on the porous base film or on the thermosensitive functional layer, wherein the heat-resistant functional layer contains a heat-resistant material. The thermally conductive material is dispersed in the heat-sensitive functional layer and / or the temperature-resistant functional layer; When applying a heat-sensitive coating slurry and / or a heat-resistant coating slurry containing a thermally conductive material, an electric field or magnetic field is applied to cause the thermally conductive material to be oriented in the vertical direction, forming an anisotropic thermally conductive network; the thermally conductive material is boron nitride, graphene, MXene, graphene oxide, or carbon nanotubes. The composite diaphragm simultaneously meets the following conditions: 3.2≤( D h × C v ) / ( T h × ε )≤8.5; 1.2≤ K v / K h ≤10; in, D h The average particle size of the thermosensitive material is... D h The range is 0.2μm to 2μm; C v The thickness of the thermally sensitive functional layer, C v The range is 1.5μm to 4μm; T h This refers to the time required for the ionic conductivity of the composite diaphragm to decrease to 10% of its initial value when the temperature reaches the melting point of the thermosensitive material during a hot chamber test. T h ≤1min, the heating rate of the hot box test is 1℃ / min~10℃ / min; ε The porosity of the porous membrane is given by [reference needed]. ε It ranges from 30% to 55%; K v The thermal conductivity of the thermally conductive material in the vertical direction is expressed in W / (m·K). K h The thermal conductivity of the thermally conductive material in the horizontal direction is expressed in W / (m·K).
2. The composite diaphragm according to claim 1, characterized in that, The thermally sensitive functional layer is disposed on both sides of the porous base membrane, and the temperature-resistant functional layer is disposed on the thermally sensitive functional layer.
3. The composite diaphragm according to claim 1, characterized in that, When the thermally conductive material is dispersed in the thermally sensitive functional layer, the composite diaphragm also satisfies the following conditions: 30≤( K v × T h × D h ) / ( C v × ε × d )≤80; in, d The average pore size of the porous membrane is expressed in μm. When the thermally conductive material is dispersed in the heat-resistant functional layer, the composite diaphragm also satisfies the following conditions: 8≤( K v × T h × D h ) / ( C v × ε × C c × d )≤50; in, C c The thickness of the heat-resistant functional layer is expressed in μm. d The average pore size of the porous base membrane is expressed in μm.
4. The composite diaphragm according to claim 1, characterized in that, The thickness of the porous base membrane L The average pore size of the porous base film is 5μm~12μm. d The micrometer diameter is 0.01 μm to 0.1 μm, and the air permeability of the porous base membrane is 60 s / 100 mL to 300 s / 100 mL.
5. The composite diaphragm according to claim 3 or 4, characterized in that, The heat-sensitive material is at least one selected from oxidized polyethylene wax, ethylene-acrylic acid copolymer, Fischer-Tropsch wax, polyurethane, ethylene-vinyl acetate, and polyethylene wax, with a melting point of 90℃~110℃, and the average particle size of the heat-sensitive material is... D h With respect to the average pore size of the porous base membrane d Satisfy: 2≤ D h / d ≤200.
6. The composite diaphragm according to claim 1, characterized in that, The thickness of the heat-resistant functional layer C c The thickness is 1.5μm to 3.5μm, and the heat-resistant functional layer contains at least one heat-resistant material selected from nano-alumina, aramid, polyimide, and nano-cellulose. The composite diaphragm has a heat shrinkage rate of less than 5% after being kept at 200°C for 1 hour. And the thickness of the thermal functional layer C v With respect to the thickness of the porous base film L The ratio satisfies: 0.15 ≤ C v / L ≤0.
45.
7. The composite diaphragm according to claim 1, characterized in that, The amount of thermally conductive material added to the thermosensitive functional layer accounts for 5% to 10% of the total mass of the thermosensitive material, and the amount of thermally conductive material added to the heat-resistant functional layer accounts for 8% to 15% of the total mass of the heat-resistant material.
8. A lithium-ion battery, characterized in that, It includes a positive electrode, a negative electrode, an electrolyte, and a composite separator as described in any one of claims 1-7.
9. A method for preparing the composite membrane as described in any one of claims 1-7, characterized in that, Includes the following steps: Thermosensitive materials, dispersants, binders and solvents are mixed to obtain a thermosensitive coating slurry; The heat-resistant material, dispersant, binder and solvent are mixed to obtain the heat-resistant coating slurry; Add the thermally conductive material to the heat-sensitive coating slurry and / or the heat-resistant coating slurry and mix evenly; The heat-resistant coating slurry and the thermosensitive coating slurry are applied to the corresponding sides of the porous base film to form a heat-resistant functional layer and a thermosensitive functional layer; the thermosensitive functional layer is disposed on at least one side of the porous base film, and the heat-resistant functional layer is disposed on the porous base film or on the thermosensitive functional layer. When applying a heat-sensitive coating slurry containing thermally conductive material and / or the heat-resistant coating slurry, an electric field or magnetic field is applied to orient the thermally conductive material in a vertical direction, and the composite membrane is obtained after drying.
Citation Information
Patent Citations
Battery diaphragm, secondary battery and electric equipment
CN116885388A
Diaphragm and electrochemical device comprising same
CN121282567A